Simulations of radiation damage as a function of the temporal pulse profile in femtosecond X‐ray protein crystallography. (24th February 2015) - Jönsson, H. Olof; Tîmneanu, Nicuşor; Östlin, Christofer; Scott, Howard A.; Caleman, Carl
<x xml:space="preserve">Abstract</x> Serial femtosecond X‐ray crystallography of protein nanocrystals using ultrashort and intense pulses from an X‐ray free‐electron laser has proved to be a successful method for structural determination. However, due to significant variations in diffraction pattern quality from pulse to pulse only a fraction of the collected frames can be used. Experimentally, the X‐ray temporal pulse profile is not known and can vary with every shot. This simulation study describes how the pulse shape affects the damage dynamics, which ultimately affects the biological interpretation of electron density. The instantaneously detected signal varies during the pulse exposure due to the pulse properties, as well as the structural and electronic changes in the sample. Here ionization and atomic motion are simulated using a radiation transfer plasma code. Pulses with parameters typical for X‐ray free‐electron lasers are considered: pulse energies ranging from 104 to 107 J cm−2 with photon energies from 2 to 12 keV, up to 100 fs long. Radiation damage in the form of sample heating that will lead to a loss of crystalline periodicity and changes in scattering factor due to electronic reconfigurations of ionized atoms are considered here. The simulations show differences in the dynamics of the radiation damage processes for different temporal pulse profiles and intensities, where ionization or atomic motion could be predominant. The different dynamics influence the recorded diffracted signal in any given resolution and will affect the subsequent structure determination.